Apuleius’ Venus and Speech Characterization - Dubova, Svetlana (Hyperboreus, 2021)
The article explores the character of Venus in Apuleius’ story of Cupid and Psyche, as well as the lexical tools used for describing her actions and conveying her speech. Venus is one of the main characters; her speeches take prominent positions in the story and require special attention. Although the phenomenon of speech characterization in Latin literature is occasional, it may be assumed that the character of Venus is distinguished by archaic vocabulary. We see a variety of words with archaic tint either used by Venus or in relation to her, but the eﬀect of surprise and novelty produced by these words is much more signiﬁcant than their number. This eﬀect is notable in Venus’ soliloquy at the beginning of the story (Met. 4. 30) and Jupiter’s address to her at the end of it (Met. 6. 23). Even though Apuleius’ characters do not have consistent voice characteristics and the archaic words are mostly spread out randomly throughout the novel, it appears that archaic vocabulary is important for the ﬁgure of Venus. The elevated language with archaic and legal touches stands in contrast to her emotional and petty behavior, improper for a powerful goddess, which enhances the eﬀect of parody.